2009
DOI: 10.1007/s10534-009-9244-1
|View full text |Cite
|
Sign up to set email alerts
|

Duality of effect of La3+ on mitochondrial permeability transition pore depending on the concentration

Abstract: In order to explore the role of mitochondria in proliferation promotion and/or apoptosis induction of lanthanum, the mutual influences between La3+ and Ca2+ on mitochondrial permeability transition pore (PTP) opening were investigated with isolated mitochondria from rat liver. The experimental results revealed that La3+ influence the state of mitochondria in a concentration-dependent biphasic manner. La3+ in nanomolar concentrations, acting as a Ca2+ analog, entered mitochondrial matrix via the RuR sensitive C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Besides the ER, the Golgi apparatus (Chandra et al 1991;Zha et al 1995) and mitochondria (Gunter et al 1994;Werth and Thayer 1994) are other important sources of intracellular Ca 2+ . La 3+ can reportedly displace mitochondrial Ca 2+ (Dong et al 2009). As shown in Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Besides the ER, the Golgi apparatus (Chandra et al 1991;Zha et al 1995) and mitochondria (Gunter et al 1994;Werth and Thayer 1994) are other important sources of intracellular Ca 2+ . La 3+ can reportedly displace mitochondrial Ca 2+ (Dong et al 2009). As shown in Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, mitochondria are both the source and target of ROS (Simon et al 2000). The previous report Dong et al 2009) and our previous studies (Shen et al 2009b, c) on [LaCit 2 ] 3-and [YbCit 2 ] 3--induced HeLa cells apoptosis have shown that cell apoptosis promoted by rare earth complexes may be related to mitochondrial apoptosis pathway and that ROS were involved in the mechanism. Similar to the result of [LaCit 2 ] 3-and [YbCit 2 ] 3-on HeLa cells, these altered proteins in [LaCit 2 ] 3--treated SiHa cells can be classified into several categories, including the proteins involved in apoptosis and cell proliferation, stress response and redox activity, and translation and protein synthesis.…”
Section: Discussionmentioning
confidence: 82%
“…Data are normalized to the density of -actin and are the mean ± SD of three independent experiments (*p < 0.05, **p < 0.01, compared with the control group). stimulation of ROS generation through interaction with mitochondria is involved in the mechanisms of cytotoxicity of lanthanide ions [17,18]. In this work, in order to explore the potential neurotoxicity of Gd 3+ , we investigated the effects of GdCl 3 on neurons both in the presence and the absence of astrocytes by use of a Transwell co-culture method as indicated in Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…Submicromolar concentrations of La 3+ have been shown to stimulate mitochondrial ROS generation by acting as a Ca 2+ analog [18] and Gd 3+ may increase ROS production in a similar way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation